Olfactory appraisal of odorants for 100% hydrogen networks. (14th April 2020) - Mouli-Castillo, Julien; Bartlett, Sam; Murugan, Arul; Badham, Pete; Wrynne, Aidan; Haszeldine, Stuart; Wheeldon, Mark; McIntosh, Angus
Abstract: To meet carbon emissions reduction targets heat and transport need to be decarbonised. Hydrogen is being considered as a flexible energy vector that could play an important part in this endeavour. With demonstration projects on the rise it is crucial to identify suitable odorants to ensure, safety regulations are met and public acceptance gained. Specifically, this work investigates the use of sulphur based odorants currently in use in the UK and Europe, alongside sulphur-free and experimental ones, for use in a 100% hydrogen gas demonstration network in the UK. Gas samples odorised with five different odorants are analysed to determine odour detection threshold, the odour intensity, its hedonic tone and character. The tests are performed by an accredited laboratory following EU standards. The results show that four odorants meet requirements as stenching agents for use in UK gas distribution network, whilst one, 5-ethylidene-2-norbornene, fails to demonstrate an unpleasant odour. Highlights: Four odorants currently in use appear suitable for a hydrogen network. 5-ethylidene-2-norbornene does not illicit an unpleasant odour. Tested odorants are intense enough to be detected as a result of a gas leak. Tested odorants display between 4 and 9 odour characters, making them distinctive. Pleasantness or unpleasantness tends to increase with increasing intensity.